Hydrogen Hub Potential in the Caribbean: Towards a Sustainable Future - Miller, Kahuina; Graham, Carolyn (Sustainable Marine Structures, 2025)
The Caribbean presents a wide range of opportunities with varying potential to contribute to the Gross National Incomes of the countries. However, the tourism industry remains a key source of income but is vulnerable to disasters and other upheavals. There are alternatives to sustainable growth such as the blue economy with the potential for hydrogen extraction from the Caribbean Sea, which can  make a significant contribution. The Caribbean Transshipment Triangle boasts significant port infrastructure that plays a crucial role in transporting goods and has the potential to become hydrogen hubs. The aim of this research is to examine the potential for countries in the region to develop this industry. A quantitative methodology was employed to examine the correlation between renewable energy and economic growth among six major transshipment countries in the Caribbean transshipment triangle, from 2010 to 2020. The study employed the Pearson correlation coefficient to analyze the data collected from these countries. The findings indicated that the Dominican Republic and Panama had the highest correlation between renewable energy and economic growth. Specifically, Jamaica, Panama, and the Dominican Republic demonstrated a moderate to high correlation between Renewable Power Capacity (RPC) and GDP. Consequently, investing in port infrastructure to facilitate hydrogen production, storage, distribution, and export could have positive effects on these economies. These findings are of interest to governments, managers, professionals, policymakers, and investors in the power generation sector. The research supports visions of a resilient blue economy and addresses sustainable development concerns in the Caribbean region. ER